History of Psychiatry and Medical Psychology With an Epilogue on Psychiatry and the Mind-Body Relation - Wallace, Edwin R.; Gach, John (Springer US : Imprint: Springer, 2008)
The first English-language comprehensive reference on the history of psychiatry since 1966. The Romans knew that Nero was insane. Shakespeare's Macbeth asked his doctor to treat "a mind diseased." The people of the European Enlightenment era pondered whether the asylum inmates were mad or simply bad. As a discipline, psychiatry has always walked a fine if not easily defined line between social and biological science. History of Psychiatry and Medical Psychology traces this evolution in its social, political, and philosophical contexts, charting the rise of psychology as a legitimate field of scientific pursuit, and of psychiatry as a medical specialty. An interdisciplinary team of noted historians (including Sander Gilman, Dora Weiner, Hannah Decker, and the recently deceased dean of American psychiatric history, George Mora) has distilled centuries of history-protracted debates, false starts, and missteps included-resulting in an engaging and inspiring narrative of history and methodology in the making. Highlights include: A prologue dealing with philosophical and methodological history as it applies to psychology and psychiatry The birth of brain science in antiquity, the Middle Ages, and the Renaissance The roots of modern psychiatry in the French Revolution Changing concepts of schizophrenia and depression The influence of neurology on psychiatry Evolutions in treatment: mental institutions, hypnotherapy, pharmacotherapy The emergence of psychoanalysis and "national psychologies" in Europe and America Modern critiques, including the chapter "Thoughts Toward a Critique of Biological Psychiatry" Its wide scope, divergent viewpoints, and insistence on viewing historical periods through their own lenses and not our own makes this History a must-have reference for scholars of psychiatry, psychology, and medicine. At the same time, it is accessible enough for the lay reader with some background in the field.